Karst landscape in terms of synergetics: general remarks - Andreychouk, V. (Спелеологія і карстологія, 2014)
Specificity of karst landscape is well known. The author proposes to look at the karst landscape as the separate evolutional stage of a karst megacycle, considered as a typical synergistic phenomenon. Специфика карстового ландшафта хорошо известна. Автор предлагает посмотреть на карстовый ландшафт как на отдельную эволюционную стадию карстового мегацикла, рассматриваемого как типичное синергетическое явление. Специфіка карстового ландшафту добре відома. Автор пропонує подивитись на карстовий ландшафт як на окрему еволюційну стадію карстового мегациклу, котрий розглядається як типове синергетичне явище.